Optimalisasi Kompetensi Penulisan Artikel Ilmiah melalui Program Pelatihan dan Pendampingan bagi Mahasiswa Universitas Hamzanwadi - Herman Wijaya; Titin Ernawati; Lalu Fakihuddin (BALE LITERASI, 2026)
The ability to write scientific articles is an essential academic competency that supports the development of a publication culture in higher education. However, preliminary observations at Universitas Hamzanwadi revealed that most students still experience difficulties in transforming their research findings into scientific articles that meet the standards of national journals. The major challenges include limited understanding of article structure, citation techniques, the use of reference management software, and the manuscript submission process through the Open Journal System (OJS). This Community Service Program (PkM) aimed to enhance students' scientific article writing competence through a structured training and mentoring program oriented toward publication outcomes. The participants were 45 students of Universitas Hamzanwadi who had completed research projects or undergraduate theses. The program was implemented in four stages: needs assessment, training, intensive mentoring, and evaluation. Data were collected through questionnaires, observations, interviews, documentation, and pretest–posttest assessments. Quantitative data were analyzed using descriptive statistics to measure improvements in participants' competencies, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The results indicated that the average competency score increased from 52.33 in the pretest to 89.43 in the posttest, representing a high level of improvement. A total of 45 scientific articles were successfully completed, 39 articles were declared ready for submission, and 32 articles were submitted to national journals through the OJS platform. In addition to improving students' writing competencies, the program produced an end-to-end mentoring model that integrates all stages of scientific publication, from manuscript preparation to journal submission. This model offers a systematic and sustainable approach to fostering students' scientific publication skills and has the potential to be replicated in other higher education institutions to strengthen the culture of academic publishing.